Decreased recent thymus emigrant number in rheumatoid factor-negative polyarticular juvenile idiopathic arthritis - Horvath, D. [UNIFESP] (2010)
ObjectivesTo determine TCR excision circle (TREC) levels, a marker of recent thymic emigrants, in the peripheral lymphocyte pool of rheumatoid factor-negative (RF circle divide) polyarticular juvenile idiopathic arthritis (JIA) children.Materials and methodsWe studied TREC levels in peripheral blood mononuclear cells (PBMC) in 30 RF circle divide polyarticular JIA children with active disease and in 30 age- and gender-matched healthy controls. Signal-joint TREC concentration was determined by real-time quantitative-PCR as the number of TREC copies/mu g PBMC DNA gauged by a standard curve with known number of TREC-containing plasmids.ResultsTREC levels in PBMC were significantly lower in JIA (4.90 +/- 3.86 x 10(4) TRECs/mu g DNA) as compared to controls (10.45 +/- 8.45 x 10(4) TRECs/mu g DNA, p=0.001). There was an inverse correlation between age and TREC levels in healthy children (r=-0.438, p=0.016) but not in JIA. No clinical association was observed between TREC levels and disease activity and use of oral steroids and methotrexate.ConclusionsThe finding of decreased PBMC TREC levels in RF circle divide polyarticular JIA children is consistent with a low proportion of recent thymus emigrants. This may interfere with the equilibrium between populations of polyclonal and naive T cells versus oligoclonal memory auto-reactive T cells and, therefore, may hinder the maintenance of immune tolerance in this disease.